PENGARUH LABEL HALAL, DESAIN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MENGGUNAKAN PRODUK KOSMETIK PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM UIN SULTHAN THAHA SAIFUDDIN JAMBI - Marissa, Nurliana; Anita, Efni; Nofriza, Eri (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
This thesis is entitled The Influence of Halal Labeling, Design and Product Quality on Purchasing Decisions to Use Cosmetic Products in Students of the Faculty of Islamic Economics and Business, UIN Sulthan Thaha Saifuddin Jambi. This study aims to determine the effect of halal labels, design and product quality simultaneously and partially on cosmetic purchasing decisions in students of the Faculty of Islamic Economics and Business. The method used in this study is descriptive quantitative, in which the data collection researchers used observation, interviews, questionnaires and documentation. The number of samples in this study were 96 students, and using a non-probability sampling technique, is a sampling technique that does not provide an opportunity for every element or member of the population to be sampled. The results of the study show that the halal label, design and product quality have a positive and significant effect on purchasing decisions. Based on data analysis in this study, these variables are valid and reliable. In testing the classical assumptions with a normal distribution, heteroscedasticity and multicollinearity do not occur.